Affinity chromatography of Ankistrodesmus braunii nitrate reductase using blue dextran-sepharose (Revista Española de Fisiología, 1980)
Blue Dextran has been coupled covalently to Sepharose-4B to purify the enzymatic complex NAD(P)H-nitrate reductase (EC 1.6.6.2) from the green alga Ankistrodesmus braunii by affinity chromatography.The optimum conditions for the accomplishment of the chromatographic process have been determined.The adsorption of nitrate reductase on Blue Dextran Sepharose is optimum when a phosphate buffer of low ionic strength and pH 6.5-7.0 is used.Once the enzyme has been bound to Blue Dextran Sepharose, it can be specifically eluted by addition of NADH and FAD to the washing buffer.However, none of the nucleotides added separately is able to promote the elution of the enzyme from the column.The elution can be also achieved, but not specifically, by increasing the ionic strength of the buffer with KCl.These results have made possible a procedure for the purification of A.braunii nitrate reductase which led to electrophoretic homogeneity, with an overall yield of 70% and a specific activity of 49 units/mg of protein.